PROFIL INTERAKSI SOSIAL RENDAH KELAS VIII DI SEKOLAH MENENGAH PERTAMA UMMUL QURO - Nurul Fauziah; Asep Samsudin; Siti Fatimah (FOKUS (Kajian Bimbingan & Konseling dalam Pendidikan), 2022)
Social interaction is a reciprocal relationship between individuals with individuals, individuals with groups, and groups with groups, in this study the subjects taken were 5 students at the junior high school level (Junior High School). Students at the junior high school level are generally included in the adolescent phase which is carrying out their developmental tasks for their environment, both in the family environment, around the house and at school. One of the student environments is the school environment where these students have social interactions with teachers, as well as with their classmates. The purpose of this study is to describe how the process of good social interaction for students who have low social interaction in class VIII SMP Ummul Quro Cihampelas during the pandemic. This research uses a qualitative approach with descriptive methods and the techniques used for data collection are observation, interviews and documentation. The results showed that the factors of low social interaction in students were having a shy nature, avoiding crowds, limiting friendships, having a psychosomatic history due to being abandoned by their parents, indifferent, happy to be alone, then the results obtained in this study are social interaction profiles. lower grade VIII at Ummul Quro junior high school.Keywords: Social Interaction,  Students